Mengatasi Masalah Komunikasi dalam Keluarga Melalui Strategic Family Therapy - Dini Fidyanti Devi (JIP (Jurnal Intervensi Psikologi), 2016)
Participants of this study were a mother and her daughter, which had a communication problem. The purpose of this study was to determine the effect of strategic family therapy in an effort to increase the adaptive communication between the daughter and her mother. The interventions hadfour sessions with a given task to be performed by each member of the family. After the intervention ended, it showed that the communication between family members became more open, aware of others needs. Each member of the family could shape a new behavior that has been agreed despite of some tasks that have not been done.Â Key words: : strategic family therapy, communication, family